K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

3 tháng 11 2021

\(\frac{2^{13}.9^4}{6^6.8^3}\)

\(=\frac{2^{13}.\left(3^2\right)^4}{\left(2.3\right)^6.\left(2^3\right)^3}\)

\(=\frac{2^{13}.3^8}{2^6.3^6.2^9}\)

\(=\frac{2^{13}.3^8}{2^{15}.3^6}\)

\(=\frac{1.3^2}{2^2.1}\)

\(=\frac{3^2}{2^2}=\frac{9}{4}\)

5 tháng 10 2017

\(\dfrac{2^{15}.9^4}{6^6.8^3}=\dfrac{2^{15}.\left(3^2\right)^4}{\left(3.2\right)^6.\left(2^3\right)^3}=\dfrac{2^{15}.3^8}{3^6.2^6.2^9}=\dfrac{2^{15}.3^6.3^2}{3^6.2^{15}}=3^2=9\)

6 tháng 9 2018

\(\frac{2^{15}\cdot9^4}{6^6\cdot8^3}=\frac{2^{15}\cdot3^4\cdot3^4}{2^6\cdot3^6\cdot\left(2^4\right)^3}=\frac{2^{12}\cdot2^3\cdot3^8}{2^6\cdot3^6\cdot2^{12}}\)

\(=\frac{2^3\cdot3^2\cdot3^6}{2^3\cdot2^3\cdot3^6}=\frac{3^3}{2^3}\)

\(=\frac{27}{8}\)

6 tháng 9 2018

\(\frac{2^{15}.9^4}{6^6.8^3}=\frac{\left(2^3\right)^5.\left(3^2\right)^4}{6^6.8^3}=\frac{8^5.3^8}{6^6.8^3}\)

\(=\frac{8^2.3^8}{6^6}=\frac{64.6561}{46656}=\frac{64.6561}{64.729}\)

\(=\frac{6561}{729}=9\)

4 tháng 8 2017

\(\dfrac{2^{15}.9^4}{6^6.8^3}=\dfrac{2^{15}.3^8}{2^6.3^6.2^9}=3^2=9\)

4 tháng 8 2017

\(\dfrac{2^{15}.9^4}{6^6.8^3}=\dfrac{2^{15}.\left(3^2\right)^4}{\left(2.3\right)^6.\left(2^3\right)^3}=\dfrac{2^{15}.3^8}{2^6.3^6.2^9}=\dfrac{3^8}{3^6}=3^2=9\)

10 tháng 10 2017

\(\dfrac{2^{15}.9^4}{6^6.8^3}=\dfrac{2^{15}.\left(3^2\right)^4}{\left(3.2\right)^6.\left(2^3\right)^3}=\dfrac{2^{15}.3^8}{3^6.2^6.2^9}=\dfrac{2^{15}.3^6.3^2}{3^6.2^{15}}=3^2=9\)

23 tháng 10 2020

\(\frac{2^{15}.9^4}{6^6.8^3}=\frac{2^{15}.\left(3^2\right)^4}{\left(2.3\right)^6.\left(2^3\right)^3}=\frac{2^{15}.3^8}{2^6.3^6.2^9}=2.3^2=2.9=18\)

1 tháng 10 2019

\(C=\frac{2^{15}.9^4}{6^6.8^3}=\frac{2^{15}.3^8}{3^6.2^6.2^9}=\frac{2^{15}.3^8}{3^6.2^{15}}=3^2=9\)

1 tháng 10 2019

C=\(\frac{2^{15}.9^4}{6^6.8^3}=\frac{2^{15}.3^8}{2^6.3^6.2^9}=\frac{2^{15}.3^8}{3^6.2^{15}}=3^2\)\(=9\)

13 tháng 11 2021

\(\dfrac{2^{13}.9^4}{6^6.8^3}=\dfrac{2^{13}.3^8}{3^6.2^6.2^9}=\dfrac{2^{13}.3^8}{3^6.2^{15}}=\dfrac{3^2}{2^2}=\dfrac{9}{4}\)

21 tháng 6 2016

\(\frac{2^{15}.9^4}{6^6.8^3}=\frac{2^{15}.\left(3^2\right)^4}{2^6.3^6.\left(2^3\right)^3}=\frac{2^{15}.3^8}{2^6.3^6.2^9}=\frac{2^{15}.3^8}{2^{15}.3^6}=\frac{1.3^2}{1.1}=3^2=9\)

13 tháng 9 2015

\(\frac{2^{15}\cdot\left(3^2\right)^4}{\left(2\cdot3\right)^6\cdot\left(2^3\right)^3}=\frac{2^{15}\cdot3^8}{2^6\cdot3^6\cdot2^9}=\frac{2^{15}.3^8}{2^{15}\cdot3^6}=\frac{3^8}{3^6}=3^2=9\)

§óng cho l ike nhÐ !